A Structured Approach to Learning Management in Piano Classes: A Case Study of Chopin’s Polonaise Op. 53 - Yuanyi, Zhu; Klaywong, Sinam (International Journal of Multidisciplinary in Management and Tourism, 2025)
This article aimed to study Learning Management in Piano Classes for Polonaise Music. The research sample consisted of three piano instructors from the Sichuan Conservatory and three second-year students from the Piano Department. Research tools included semi-structured academic interviews along with classroom observations. The study employed qualitative methods, with data collection focusing on both interviews and classroom observations. The findings revealed that The Polonaise in A-flat Major, Op. 53 (Heroic), composed by Chopin in 1842, is renowned for its grandeur, patriotism, and resilience. This piece follows a ternary form (A-B-A) with a 3/4 rhythm, expansive arpeggios, and sweeping octaves, symbolizing Poland’s struggle for liberation. It serves as a powerful symbol of Polish nationalism. The learning management of The Polonaise in A-flat Major, Op. 53, which is structured in ternary form and set in a ¾ time signature, is effectively integrated into piano classroom instruction to enhance piano performance skills and cultural interpretation. The learning process emphasizes well-structured principles and lesson plans, incorporating lecture-based teaching, demonstrative methods, cooperative learning, and interactive sessions. The assessment focuses on four key components: Practical Performance (50%), Learning Management Achievement (30%), Positive Character Traits (10%), and Class Attendance (10%). This approach effectively develops students’ technical skills, cultural appreciation, positive character traits, critical thinking, and musical interpretation, fostering well-rounded and comprehensive musical education.